2015
DOI: 10.1007/s13364-015-0245-x
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural land-use intensity and its effects on small mammals in the central region of Argentina

Abstract: Your article is protected by copyright and all rights are held exclusively by Mammal Research Institute, Polish Academy of Sciences, Bia#owie#a, Poland. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…The occurrence of the specialist species A. azarae in more vegetated and stable habitats is in line with previous studies of this species (Andreo et al, 2009;Busch et al, 2001;Gomez et al, 2015). Marchand et al (2003) found that individuals belonging to the specialist species Myodes glareolus had lower degree of FA in the more extensive and more connected hedges of undisturbed areas than in fragmented hedgerows of disturbed areas.…”
Section: Speciessupporting
confidence: 90%
“…The occurrence of the specialist species A. azarae in more vegetated and stable habitats is in line with previous studies of this species (Andreo et al, 2009;Busch et al, 2001;Gomez et al, 2015). Marchand et al (2003) found that individuals belonging to the specialist species Myodes glareolus had lower degree of FA in the more extensive and more connected hedges of undisturbed areas than in fragmented hedgerows of disturbed areas.…”
Section: Speciessupporting
confidence: 90%
“…Although resident females of A. azarae were always much more aggressive than intruders, the rates of aggressive behaviour exhibited by them never reached the highest values registered in females of Calomys musculinus (Steinmann et al 2009). Calomys musculinus, a promiscuous cricetid rodent commonly known as corn mice, is numerically dominant in the Pampean agrarian ecosystems of central Argentina, together with A. azarae (Steinmann et al 2009;Gomez et al 2015). Meanwhile in our study, A. azarae resident females spent 30% of the total time of each trial in aggressive displays and C. musculinus resident females spent more than 80% exhibiting aggressive behaviours against intruder females (Steinmann 2006;Steinmann et al 2009).…”
Section: Discussionmentioning
confidence: 49%
“…; Gomez et al. ). Meanwhile in our study, A. azarae resident females spent 30% of the total time of each trial in aggressive displays and C. musculinus resident females spent more than 80% exhibiting aggressive behaviours against intruder females (Steinmann ; Steinmann et al.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations